Association of onset to balloon and door to balloon time with long term clinical outcome in patients with ST elevation acute myocardial infarction having primary percutaneous coronary intervention: observational study. (23rd May 2012) - Shiomi, Hiroki; Nakagawa, Yoshihisa; Morimoto, Takeshi; Furukawa, Yutaka; Nakano, Akira; Shirai, Shinichi; Taniguchi, Ryoji; Yamaji, Kyohei; Nagao, Kazuya; Suyama, Tamaki; Mitsuoka, Hirokazu; Araki, Makoto; et al.
Abstract : Objective To evaluate the relation of symptom onset to balloon time and door to balloon time with long term clinical outcome in patients with ST segment elevation myocardial infarction (STEMI) having primary percutaneous coronary intervention. Design Observation of large cohort of patients with acute myocardial infarction. Setting 26 tertiary hospitals in Japan. Participants 3391 patients with STEMI who had primary percutaneous coronary intervention within 24 hours of symptom onset. Main outcome measures Composite of death and congestive heart failure, compared by onset to balloon time and door to balloon time. Results Compared with an onset to balloon time greater than 3 hours, a time of less than 3 hours was associated with a lower incidence of a composite of death and congestive heart failure (13.5% (123/964) v 19.2% (429/2427), P<0.001; relative risk reduction 29.7%). After adjustment for confounders, a short onset to balloon time was independently associated with a lower risk of the composite endpoint (adjusted hazard ratio 0.70, 95% confidence interval 0.56 to 0.88; P=0.002). However, no significant difference was found in the incidence of a composite of death and congestive heart failure between the two groups of patients with short (≤90 minutes) and long (>90 minutes) door to balloon time (16.7% (270/1671) v 18.4% (282/1720), P=0.54; relative risk reduction 9.2%). After adjustment for confounders, no significant difference was seen in the risk of the composite endpoint between the two groups of patients with short and long door to balloon time (adjusted hazard ratio: 0.98, 0.78 to 1.24: P=0.87). A door to balloon time of less than 90 minutes was associated with a lower incidence of a composite of death and congestive heart failure in patients who presented within 2 hours of symptom onset (11.9% (74/883) v 18.1% (147/655), P=0.01; relative risk reduction 34.3%) but not in patients who presented later (19.7% (196/788) v 18.7% (135/1065), P=0.44; −5.3%). Short door to balloon time was independently associated with a lower risk of a composite of death and congestive heart failure in patients with early presentation (adjusted hazard ratio 0.58, 0.38 to 0.87; P=0.009) but not in patients with delayed presentation (1.57, 1.12 to 2.18; P=0.008). A significant interaction was seen between door to balloon time and time to presentation (interaction P=0.01). Conclusions Short onset to balloon time was associated with better 3 year clinical outcome in patients with STEMI having primary percutaneous coronary intervention, whereas the benefit of short door to balloon time was limited to patients who presented early. Efforts to minimise onset to balloon time, including reduction of patient related delay, should be recommended to improve clinical outcome in STEMI patients.